2012
DOI: 10.1177/1471301212446111
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the psychometric properties and efficacy of Dementia Care Mapping

Abstract: This paper offers a critique of Dementia Care Mapping (DCM) as a practice development and research tool by examining the psychometric properties and efficacy of DCM as a method for evaluating and enhancing care quality and quality of life. Based on a review and analysis of the published empirical studies utilizing DCM, it becomes apparent that there is mixed support for the tool's validity and reliability. More importantly, there is a need for additional studies specifically examining the range of related asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…() reported that DCM has good internal consistency, test–retest reliability and concurrent validity, correlating well with measures of quality of life, while others have been critical of DCM, raising concerns about reliability and validity (Thornton et al . ; Cooke & Chaudhury ), and suggesting that DCM may be inferior to some existing validated measures of well‐being (Chenoweth & Jeon ). However, others have successfully used DCM to evaluate care and support practices within services for people with IDs (Persaud & Jaycock ; Jaycock & Persaud ; Jaycock et al .…”
Section: Methodsmentioning
confidence: 99%
“…() reported that DCM has good internal consistency, test–retest reliability and concurrent validity, correlating well with measures of quality of life, while others have been critical of DCM, raising concerns about reliability and validity (Thornton et al . ; Cooke & Chaudhury ), and suggesting that DCM may be inferior to some existing validated measures of well‐being (Chenoweth & Jeon ). However, others have successfully used DCM to evaluate care and support practices within services for people with IDs (Persaud & Jaycock ; Jaycock & Persaud ; Jaycock et al .…”
Section: Methodsmentioning
confidence: 99%
“…The data regarding resident activities were collected using an adapted version of the DCM (33). The original DCM is widely used in dementia care (36)(37)(38). The adapted version emphasises activities can be used to observe people with or without dementia and has been validated against measures of well-being and quality of life among older people (39).…”
Section: Methodsmentioning
confidence: 99%
“…The need to establish IRR between DCM users has been discussed by a number of previous studies (10,11,20), however, this is the first study, to examine if those trained in DCM are conducting regular IRR maps, if so how frequently and if not what the barriers to this are. Encouragingly, of those who had mapped only 20% never carried out IRR checks with the biggest barrier to doing this being a lack of someone else to complete IRR with.…”
Section: Discussionmentioning
confidence: 99%
“…DCM guidance (2) recommends that mappers establish inter-rater reliability (IRR) (minimum 70% concordance across BCC and ME values) with any co-mapper ahead of use, and that every mapper conduct an IRR map at least once per year. Published literature highlights that while a number of research studies have examined IRR and demonstrated it can be established effectively between experienced mappers in research contexts (10,20), relatively little is really known about IRR between mappers in everyday practice or whether IRR checks are completed regularly (19). In one study, Thornton et al examined IRR in the context of everyday mapping.…”
Section: Dementia Care Mappingmentioning
confidence: 99%